All Days 2004
DOI: 10.2118/86504-ms
|View full text |Cite
|
Sign up to set email alerts
|

Diversion and Cleanup Studies of Viscoelastic Surfactant-Based Self-Diverting Acid

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractA self-diverting-acid based on viscoelastic surfactant (SDVA) has been used recently on stimulation treatments of carbonate formations. The new system has been proven successfull in more than 250 field applications. The decrease of acid concentration during the spending process viscosifies the fluid by the transformation from spherical micelles to an entangled wormlike micellar structure while penetrating the carbonate rock. The highly viscous fluid acts as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…The idea is that, by increasing the viscosity, injection pressure will rise in the wellbore resulting in better coverage along the wellbore. In particular, self-diverting acids 13 have been developed such that, as acid spends and wormholes propagate in a higher injectivity region of the reservoir, the acid temporarily thickens significantly, resulting in partial diversion of the acid into zones of initially lower injectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The idea is that, by increasing the viscosity, injection pressure will rise in the wellbore resulting in better coverage along the wellbore. In particular, self-diverting acids 13 have been developed such that, as acid spends and wormholes propagate in a higher injectivity region of the reservoir, the acid temporarily thickens significantly, resulting in partial diversion of the acid into zones of initially lower injectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The viscoelasticity of solution does not develop until the acid reacts with carbonate in the formation (in this article, we use sodium salicylate to produce gel). The increases in Ca 2+ ions and pH due to the HCl-carbonate reaction caused in situ gelling of the acid [22]. The high viscosity temporarily blocks the wormholes formed in the rock matrix, allowing the acid to cover the unacidized area.…”
Section: Rheological Measurementsmentioning
confidence: 99%
“…Lungwitz et al (2007) studied a viscoelastic acid system in core floods that increases in viscosity as acid is spent. While self-diverting fluids are typically thought to be most useful in acid-fracturing applications, Majdi et al (2003) found that visco-elastic self-diverting acid was highly effective for matrix acidizing in a field study involving multi-layered carbonate structures (3md to 400md).…”
Section: Non-newtonian Fluidsmentioning
confidence: 99%